Role of perioperative nursing in anesthesia: a national overview - Cassiane de Santana Lemos; Vanessa de Brito Poveda (SciELO, 2022)
Abstract Objectives: To assess the actions performed by the operating room nurse during anesthesia and their behavior for patient safety regarding the reporting on adverse events, and to analyze their knowledge about anesthetic practices. Method: This is a cross-sectional study carried out using an electronic questionnaire consisting of socio-demographic, professional practice, knowledge in anesthesia, patient safety, and professional practice questions, conducted from January to March 2019 with operating room nurses. Results: One hundred nurses participated, 89 (89%) being women, with a mean age of 41.09 years (SD = 9.36), time of undergraduate completion of 14.33 years (SD = 8.34). The average attendance was 4.69 operating rooms (SD = 2.07) per nurse, with an emphasis on action before induction (49; 49%). Professionals reported performance of simultaneous activities (72; 72%) and insufficient number of employees (57; 57%) as difficulties of their daily practice. Among the participants, 77 (77%) correctly cited the periods of general anesthesia and 80.4% always reported the occurrence of an adverse event. Conclusion: Nurses identified their role in anesthesia, with limitations for assistance from multiple activities and lack of professionals.